2016
DOI: 10.34105/j.kmel.2016.08.037
|View full text |Cite
|
Sign up to set email alerts
|

Virtual team learning: The role of collaboration process and technology affordance in team decision making

Abstract: The study examines two dimensions that impact virtual team decision making. One is the influence of collaboration process structure: the sequences, patterns, and routines participants use to interact and solve problems. The other is technology affordance: the strengths and weaknesses of technologies in terms of the usefulness they offer to teams when performing tasks. Some teams used a structured collaboration process with monitoring, coordination, and backup functions during a decision-making discussion. Othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Media richness theory has shown that, for an organization to be successful, it must be able to process information in an appropriately rich format to reduce uncertainty and clarify ambiguity. Limiting ICT use in virtual teams will limit the quality and quantity of information shared between team members [5]. We can see from the above literature that ICT has a direct effect on VT decision-making processes, especially when selecting the appropriate media for communicating in the process of decision making.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Media richness theory has shown that, for an organization to be successful, it must be able to process information in an appropriately rich format to reduce uncertainty and clarify ambiguity. Limiting ICT use in virtual teams will limit the quality and quantity of information shared between team members [5]. We can see from the above literature that ICT has a direct effect on VT decision-making processes, especially when selecting the appropriate media for communicating in the process of decision making.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most studies on language differences have found a negative effect on VT decision making [4]. Based on a review of 400 organizational decisions, it was found that more than half of these decisions failed to reach their full potential due to the improper use of the ICT tools [5]. This presents a critical problem for organizations since the purpose of implementing virtual teams is to benefit from the full knowledge package of all team members and to enhance decision making.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Decision-making processes (Cordes 2016;Johnson et al 2018;Oesch and Dunbar 2018;Wei et al 2017) (Task and Relationship) Conflict (Chang et al 2014;Cordes 2016;Plotnick et al 2016) Transformational Leadership (Acai et al 2018;Derven 2016;Gibbs et al 2017;Plotnick et al 2016;Al Zain et al 2018) Cultural Intelligence (Derven 2016;Gao et al 2016;Gibbs et al 2017;Li et al 2017) Decision-Making Process. Decision-making processes are the act of processing information to reach a judgment regarding a problem.…”
Section: Factor Authorsmentioning
confidence: 99%
“…Decisions that are made after information collection and analysis are found to be more effective, which is the key point differentiating successful performing teams and unsuccessful performing teams. Scholars (Cordes 2016;Johnson et al 2018;Oesch and Dunbar 2018;Wei et al 2017) found that successful teams tend to analyze the problem in depth before taking a decision about the solution, which is not the case in unsuccessful teams (Wei et al 2017). In the next paragraphs, we review the factors that affect decision-making processes.…”
Section: Factor Authorsmentioning
confidence: 99%